Evaluating targeting efficiency of government programmes: International comparisons - Nanak Kakwani; Hyun H. Son (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper suggests how the targeting efficiency of government programmes may be better assessed. Using the `pro-poor policy' (PPP) index developed by authors, the study investigates the pro-poorness of not only government programmes geared to the poorest segment of the population, but also basic service delivery in education, health and infrastructure. This paper also shows that the targeting efficiency for a particular socioeconomic group should be judged on the basis of a `total-group PPP index', to capture the impact of operating a programme within the group. Using micro-unit data from household surveys, the paper presents a comparative analysis for Thailand, Russia, Vietnam and 15 African countries. – targeting ; pro-poor growth ; poverty
Keywords: C15; I32; 330; Armutspolitik; Thailand; Russland; Vietnam; Afrika